2019
DOI: 10.1029/2018jb016582
|View full text |Cite
|
Sign up to set email alerts
|

Lateral and Vertical Heterogeneity in the Lithospheric Mantle at the Northern Margin of the Pannonian Basin Reconstructed From Peridotite Xenolith Microstructures

Abstract: This study analyzes the microstructures and deformational characteristics of spinel peridotite xenoliths from the Nógrád-Gömör Volcanic Field (NGVF), located on the northern margin of a young extensional basin presently affected by compression. The xenoliths show a wide range of microstructures, bearing the imprints of heterogeneous deformation and variable degrees of subsequent annealing. Olivine crystal preferred orientations (CPOs) have dominantly [010]-fiber and orthorhombic patterns. Orthopyroxene CPOs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 108 publications
2
9
0
Order By: Relevance
“…This is in agreement with the fact that the xenoliths of the Nógrád-Gömör volcanic field do not show evidence of depth-related layering in terms of their petrography or LPO. In contrast, the variability in their texture and composition was attributed to the different ages and spatial distribution (Liptai et al, 2017(Liptai et al, , 2019. However, in the central and southern regions of the western CPR, including basin areas and the transition zone towards the Eastern Alps, more stations indicate multi-layered anisotropy, especially in the vicinity of Lake Balaton (Fig.…”
Section: Comparison Of Seismic Data From Shear-wave Splitting and Man...mentioning
confidence: 96%
See 3 more Smart Citations
“…This is in agreement with the fact that the xenoliths of the Nógrád-Gömör volcanic field do not show evidence of depth-related layering in terms of their petrography or LPO. In contrast, the variability in their texture and composition was attributed to the different ages and spatial distribution (Liptai et al, 2017(Liptai et al, , 2019. However, in the central and southern regions of the western CPR, including basin areas and the transition zone towards the Eastern Alps, more stations indicate multi-layered anisotropy, especially in the vicinity of Lake Balaton (Fig.…”
Section: Comparison Of Seismic Data From Shear-wave Splitting and Man...mentioning
confidence: 96%
“…In the Styrian Basin and the Nógrád-Gömör volcanic fields, the texture and deformation patterns of the xenoliths did not show evidence for multiple layers in the mantle with different orientation (Aradi et al, 2017;Liptai et al, 2019). Therefore, these authors assumed a single anisotropic layer and concluded that the most realistic scenario is a vertical foliation and horizontal lineation, with a NW-SE orientation.…”
Section: Seismic Studies On Mantle Xenolithsmentioning
confidence: 97%
See 2 more Smart Citations
“…Postkinematic percolation of the pyroxenite-producing melts can be excluded, because it implies near solidus conditions associated with the presence of reactive interstitial melts, which would result in fast annealing of the plastic deformation structures through recovery and static recrystallization processes in the peridotites (e.g., Aradi et al, 2017;Hidas et al, 2016;Liptai et al, 2019;Rampone et al, 2010;Tommasi et al, 2008). Moreover, although melt percolation controlled by the preexisting structure of the peridotites has been proposed to explain small-scale features, for instance, the orientation of mm-scale websterite lenses within harzburgite in the Lherz massif (Le Roux et al, 2008), such anisotropic percolation cannot play a major role when large melt/rock ratios are at play.…”
Section: Timing and Relationship Between Melt Infiltration And Deform...mentioning
confidence: 99%